Landslides in Malaysia : occurrences, assessment, analyses and remediation - Kim Huat, Bujang; Ali, Faisal; Baker, David H.; Singh, Harwant; Omar, Husaini (Universiti Putra Malaysia Press, 2008)
Landslides of massive mass of soil and rock debris moving downhill have emerged as a perilous geologic hazard resulting in damage to property into billions of dollars annually in addition to loss of life. This traditional domain of geomorphology has become a critical area of study for geotechnical engineers as slope instability whose prevention has to be factored into engineering design. The rapid expansion of development up slopes due to various pressures has caused sharp proliferation of hill slopes problems/landslides which were imminent due to the absence of prior experience of such engineering failures or lack of simple awareness. This book is especially written to expose the practice of safe engineering investigation design on potentially susceptible slope. The nature, occurrences, assessments, analyses and "state of the art' engineering remediation/preventive solutions for dealing with landslides especially in the tropical regions are covered in this book with the hope that it will serve as a useful guide for understanding and designing of slopes and stabilization works in both rock and soils.